2011
DOI: 10.1038/nature10508
|View full text |Cite
|
Sign up to set email alerts
|

ATM controls meiotic double-strand-break formation

Abstract: In many organisms, developmentally programmed double-strand breaks (DSBs) formed by the SPO11 transesterase initiate meiotic recombination, which promotes pairing and segregation of homologous chromosomes1. Because every chromosome must receive a minimum number of DSBs, attention has focused on factors that support DSB formation2. However, improperly repaired DSBs can cause meiotic arrest or mutation3,4, thus having too many DSBs is likely as deleterious as having too few. Only a small fraction of SPO11 protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
336
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 240 publications
(361 citation statements)
references
References 28 publications
22
336
2
Order By: Relevance
“…Consistent with our results in mouse somatic cells, however, recent studies have shown that ATM is not required for meiotic recombination, like when Spo11 gene dosage is reduced (50), but rather, that ATM plays an important role in regulating DSB levels during meiosis (51). In mitotically dividing cells, ATM has been reported to suppress spontaneous homologous recombination (52,53); increased recombination in the absence of ATM may result from increased numbers of lesions from defective DNA damage signaling or repair.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with our results in mouse somatic cells, however, recent studies have shown that ATM is not required for meiotic recombination, like when Spo11 gene dosage is reduced (50), but rather, that ATM plays an important role in regulating DSB levels during meiosis (51). In mitotically dividing cells, ATM has been reported to suppress spontaneous homologous recombination (52,53); increased recombination in the absence of ATM may result from increased numbers of lesions from defective DNA damage signaling or repair.…”
Section: Discussionsupporting
confidence: 89%
“…The uterine lining does not show evidence of proliferation or degeneration, and there is no estrous cycling (24). This may be attributed to Atm control of the number of meiotic double-strand-break (DSB) created by Spo11, important for meiotic recombination during gametogenesis in spermatogonia and priomordial follicle (23,24,30). This mechanism may partially explain the finding of sexual dimorphism: in males, disruption of meiosis would be expected to affect mainly spermatogenesis, while testosterone production by Leydig cells would not be affected.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore postulate that ATR negatively regulates DMC1 abundance by limiting its deposition to only one end of a processed meiotic DSB site and by preventing the formation of supernumerary meiotic DSBs. Two recent publications demonstrate that ATM also acts as a negative regulator of meiotic DSB formation in mouse and fly (Joyce et al, 2011;Lange et al, 2011). Further efforts are needed to clarify to what extent ATM and ATR negatively control meiotic DSB formation in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%